A rare cause of axillary swelling - Moreira, Mafalda (2022)
Axillary swelling is a common condition in pediatric age. The most common diagnosis is lymph node swelling, but it can also be caused by soft tissue tumors, vascular lesions, or inflammation of sweat glands. In rare cases, it can be due to ectopic breast tissue (EBT). A 14-year-old female presented with right axillary pain with one year of evolution and swelling for the past two months, gradually increasing in size, especially during menstruation. Sonography revealed EBT in both axillae, and further study showed duplication of the excretory system in both kidneys. The tissue on the right axilla was excised. EBT should be considered in the differential diagnosis of axillary swelling in adolescents and young females. When the diagnosis is established, the presence of associated urologic anomalies should be investigated. Clinicians should be aware that EBT can undergo the same pathological changes as normally located breast tissue. Surgical removal should be considered for cosmetic and prophylactic treatment.